Social work : past, present and future - Bamford, Terry; Bilton, Keith (Policy Press, 2020)
This collection brings together a collection of experts from across social work who explore key developments in the field over the last fifty years. They examine evolution in thinking and approaches to practice, key legislative developments, the impacts of major inquiries and look at future directions for progress in the field.